Effects of different management strategies on long‐term trends of Australian threatened and near‐threatened mammals. Issue 2 (27th January 2023) - Tulloch, Ayesha I. T.; Jackson, Micha V.; Bayraktarov, Elisa; Carey, Alexander R.; Correa‐Gomez, Diego F.; Driessen, Michael; Gynther, Ian C.; Hardie, Mel; Moseby, Katherine; Joseph, Liana; Preece, Harriet; Suarez‐Castro, Andrés Felipe; et al.
Abstract: Monitoring is critical to assess management effectiveness, but broadscale systematic assessments of monitoring to evaluate and improve recovery efforts are lacking. We compiled 1808 time series from 71 threatened and near‐threatened terrestrial and volant mammal species and subspecies in Australia (48% of all threatened mammal taxa) to compare relative trends of populations subject to different management strategies. We adapted the Living Planet Index to develop the Threatened Species Index for Australian Mammals and track aggregate trends for all sampled threatened mammal populations and for small (<35 g), medium (35–5500 g), and large mammals (>5500 g) from 2000 to 2017. Unmanaged populations (42 taxa) declined by 63% on average; unmanaged small mammals exhibited the greatest declines (96%). Populations of 17 taxa in havens (islands and fenced areas that excluded or eliminated introduced red foxes [ Vulpes vulpes ] and domestic cats [ Felis catus ]) increased by 680%. Outside havens, populations undergoing sustained predator baiting initially declined by 75% but subsequently increased to 47% of their abundance in 2000. At sites where predators were not excluded or baited but other actions (e.g., fire management, introduced herbivore control) occurred, populations of small and medium mammals declined faster, but large mammals declined more slowly, than unmanaged populations. Only 13% of taxa had data for both unmanaged and managed populations; index comparisons for this subset showed that taxa with populations increasing inside havens declined outside havens but taxa with populations subject to predator baiting outside havens declined more slowly than populations with no management and then increased, whereas unmanaged populations continued to decline. More comprehensive and improved monitoring (particularly encompassing poorly represented management actions and taxonomic groups like bats and small mammals) is required to understand whether and where management has worked. Improved implementation of management for threats other than predation is critical to recover Australia's threatened mammals. Abstract : Efectos de diferentes estrategias de manejo sobre las tendencias a largo plazo de los mamíferos amenazados y casi amenazados de Australia Resumen: El monitoreo es fundamental para evaluar la efectividad del manejo, aunque faltan evaluaciones sistemáticas y a gran escala de este monitoreo para evaluar y mejorar los esfuerzos de recuperación. Compilamos 1, 808 series temporales de 71 especies y subespecies de mamíferos terrestres y voladores amenazadas y casi amenazadas en Australia (48% de todos los taxones de mamíferos amenazados) para comparar las tendencias relativas de las poblaciones sujetas a diferentes estrategias de manejo. Adaptamos el Índice Planeta Vivo para desarrollar el Índice de Especies Amenazadas para los Mamíferos Australianos y así rastrear las tendencias agregadas de todas las poblaciones muestreadas de mamíferos amenazados y de los mamíferos pequeños (<35 g), medianos (35–5, 500 g) y grandes (>5, 500 g) entre 2000 y 2017. Las poblaciones sin manejo (42 taxones) declinaron en un 63% en promedio; los mamíferos pequeños sin manejo exhibieron las declinaciones más marcadas (96%). Las poblaciones de 17 taxones incrementaron 680% en los refugios (islas o áreas encercadas que excluían o eliminaban al zorro rojo [ Vulpes vulpes ] y al gato doméstico [ Felis catus ], especies introducidas) Afuera de los refugios, las poblaciones sometidas al cebado constante de los depredadores en un inicio declinaron en un 75% pero después incrementaron al 47% de su abundancia para el 2000. En los sitios en donde los depredadores no fueron excluidos o cebados sino sometidos a otras acciones (manejo del fuego, control de herbívoros introducidos), las poblaciones de los mamíferos pequeños y medianos declinaron más rápido, pero los mamíferos grandes declinaron de manera más lenta que las poblaciones sin manejo. Sólo el 13% de los taxones contaron con datos para sus poblaciones con y sin manejo; las comparaciones entre índices para este subconjunto mostraron que los taxones con poblaciones en incremento dentro de los refugios declinaron afuera de éstos, pero los taxones con poblaciones sujetas al cebado de depredadores afuera de los refugios declinaron más lentamente que las poblaciones sin manejo y después incrementaron, mientras que las poblaciones sin manejo continuaron su declinación. Se requiere un monitoreo más completo y mejorado (particularmente el que engloba las acciones de manejo mal representadas y los grupos taxonómicos como los murciélagos y los mamíferos pequeños) para entender si ha funcionado el manejo y en dónde. La implementación mejorada del manejo para las amenazas distintas a la depredación es fundamental para recuperar a los mamíferos amenazados de Australia. 【摘要】: 监测对于评估保护管理有效性至关重要, 但目前仍缺乏对监测的大尺度系统评估, 以评价和提高恢复工作。本研究整理了澳大利亚71种受威胁或近危的陆生及飞行野生哺乳动物物种和亚种(占所有受威胁哺乳动物的48%)的1808个时间序列, 以比较受到不同管理策略影响的种群的相对趋势。我们基于"地球生命力指数(Living Planet Index)"开发了"澳大利亚哺乳动物受威胁物种指数", 并追踪了2000‐2017年所有采样的受威胁哺乳动物种群以及小型(<35克)、中型(35‐5500克)和大型哺乳动物(>5500克)的总体趋势。结果表明, 未受到管理的种群(42个类群)数量平均减少了63%;未受到管理的小型哺乳动物种群数量下降幅度最大(96%)。17个在避难所(驱除或消灭了外来赤狐[ Vulpes vulpe ]及家猫[ Felis catus ]的岛屿和围栏区)中生活的类群种群数量增加了680%。在避难所外, 受到持续捕食者诱捕管理的种群最初数量下降了75%, 但随后增加到2000年种群数量的47%。在没有驱除或诱捕捕食者, 但采取了其它行动(如火灾管理、引入食草动物控制)的位点, 小型和中型哺乳动物种群比没有受到管理的种群下降得更快, 但大型哺乳动物相比下降得更慢。只有13%的类群同时有未受到管理种群和受到管理种群的数据, 这部分数据的指数比较显示, 在避难所内种群增加的类群在避难所外种群有所下降, 但在避难所外受到捕食者诱捕的种群比没有管理的种群下降更慢且随后种群数量增加, 而未受到管理的种群则持续下降。未来还需要更全面和更好的监测工作(特别是纳入没有得到充分代表的管理行动及类群, 如蝙蝠和小型哺乳动物), 以了解管理的有效性以及有效的区域。进一步落实对捕食以外威胁的管理措施, 对于澳大利亚受威胁哺乳动物恢复至关重要。【翻译:胡怡思;审校:聂永刚】